2015
DOI: 10.1007/s11896-015-9171-8
|View full text |Cite
|
Sign up to set email alerts
|

Brief Mental Skills Training Improves Memory and Performance in High Stress Police Cadet Training

Abstract: Psychological performance training has been shown to mitigate the negative effects of stress for police officers. We contributed to this body of evidence using techniques in breathing, mental performance imagery, and attentional focus. One group (experimental) of police academy cadets was trained in these techniques to deal with the stressful event of being sprayed with oleoresin capsicum (OC). Their physiological and behavioral responses to the event were compared to a control group of cadets. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 9 publications
0
18
0
1
Order By: Relevance
“…More specifically, the occupational performance literature has accumulated promising evidence of the cognitive attributes that are considered both trainable and capable of producing reliable performance gains for the end-user-be it an athlete (Morris and Summers, 2004;Fadde and Zaichkowsky, 2018), police officer (Page et al, 2016), first-responder (Joyce et al, 2019), or a warfighter (Adler et al, 2015;Cooper and Fry, 2018;Blacker et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the occupational performance literature has accumulated promising evidence of the cognitive attributes that are considered both trainable and capable of producing reliable performance gains for the end-user-be it an athlete (Morris and Summers, 2004;Fadde and Zaichkowsky, 2018), police officer (Page et al, 2016), first-responder (Joyce et al, 2019), or a warfighter (Adler et al, 2015;Cooper and Fry, 2018;Blacker et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although reviews of intervention studies—targeting stress and behavioral risk factors for poor health outcomes—found multiple weaknesses in design and limited impact (Lees et al., 2019; MacMillan et al., 2017; Patterson et al., 2012; Rachele et al., 2014; Wolkow et al., 2013), the level of attention to developing working models for integration into law enforcement agencies is promising. For example, psychological skill training may have an impact on officers’ memory (Page et al., 2016), and research assessing the impact of workplace resilience training also points to moderate effectiveness (Leppin et al., 2014; Vanhove et al., 2016) across sectors and for police performance (e.g., Andersen & Gustafsberg, 2016). The current study adds to the field of prevention in terms of identifying psychological, physical, and behavioral comorbidities requiring attention.…”
Section: Discussionmentioning
confidence: 99%
“…Another investigation on the efficacy of two 75-min breathing, imagery, and attentional control training sessions found improved memory for details during a stressful OC training drill compared to controls. However, training did not improve autonomic stress responses, and the authors did not report post-training performance results (Page et al, 2016). While these findings suggest a modest added benefit of mental skills training to motor learning paradigms, direct comparison of different learning strategies have shown that combined physical and mental practice is not as effective in training procedural skills compared to 100% physical practice (Hird et al, 1991).…”
Section: Bridging the Gap Between Science And Practice: Evidence-basementioning
confidence: 99%